Cyclic peptides bearing the d‐Phe‐2‐Abz turn motif: Structural characterization and antimicrobial potential. (6th December 2020) - Varnava, Kyriakos G.; Edwards, Patrick J.B.; Cameron, Alan J.; Harjes, Elena; Sarojini, Vijayalekshmi
Abstract : The effect on secondary structure and antimicrobial activity of introducing different cyclic constraints in linear β‐hairpin antimicrobial peptides has been investigated with the intention of generating cyclic β sheets as promising antimicrobials with improved therapeutic potential. The linear peptides were cyclized head to tail either directly or after the addition of either a second turn motif or a disulfide bridge. The propensity of these peptides to adopt a cyclic β‐sheet structure has been correlated to their antibacterial activity. All cyclic peptides showed enhanced activity, compared with their linear counterparts against methicillin‐resistant Staphylococcus aureus . Scanning electron microscopy and transmission electron microscopy studies showed that this family kills bacteria through membrane lysis. The peptide that showed the best efficacy against all strains (exhibiting nanomolar activity), while retaining low haemolysis, bears two symmetrical, homochiral d ‐phe‐2‐Abz‐d ‐ala turns and adopted a flexible structure. Its twin peptide that bears heterochiral turns (one with d ‐ala and one with L‐Ala) showed reduced antibacterial activity and higher percentage of haemolysis. Circular dichroism and nuclear magnetic resonance spectroscopy indicate that heterochirality in the two turns leads to oligomerization of the peptide at higher concentrations, stabilizing the β‐sheet secondary structure. More rigid secondary structure is associated with lower activity against bacteria and loss of selectivity. Abstract : d ‐Phe‐2‐Abz turn containing cyclic peptides cause bacterial cell death through cell wall damage.